(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This article discusses the formation and development of a special purpose language that has recently appeared in linguistics. It is necessary to integrate the results of language research into the educational process of modern Kazakhstan into a special, purposeful, comprehensive, pragmatic intercultural communication that meets modern requirements. One of such directions is the special purpose language in Russian NCC, English (LSP). This article describes the reasons for the emergence of the language, the factors influencing it, its scientific and terminological character. Functional style of the special purpose language, its connection with the register, genre features, lexical units, conjugation of words, words from other language combinations, numerical and artificial symbols, terms of literary language, use of professional slang.